Sensory Quality Analysis, Consumer Acceptability, and Business Start-up of Bakpia Gurih Sambal Matah - Fadilah, Muhamad; Nabilah, Zahrah Salwa; Hansa, Nayla; Alsuhendra, Alsuhendra; Ridawati, Ridawati (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to analyze the sensory characteristics of savory bakpia with tuna and sambal matah flavored tempeh filling in various filling percentages, namely 30%, 40%, and 50%. The background of this research is the desire to bring innovation to new flavors of bakpia products, which have been dominated by sweet flavors. The research method used was experimental, with sensory tests conducted by 10 expert panelists on the aspects of color, aroma, taste, and texture. The results showed that bakpia with sambal matah filling of 40% had the highest average value in almost all sensory aspects, making it the most preferred formulation. Tests were also conducted with consumer panelists to determine which percentage of sambal matah was most preferred. The results of consumer acceptance obtained the type of percentage preferred by consumers, namely the 40% chili sauce matah treatment. This product was developed in the form of a business startup with the trademark “Bakkate” and marketed through social media such as WhatsApp, Instagram, and TikTok. Consumer satisfaction analysis revealed high satisfaction levels, particularly in taste (92%), packaging design (92%), and customer service friendliness (90.6%). Other aspects such as pricing, ease of purchase, and delivery speed were also positively rated above 84%. Financial analysis indicated that with a selling price of IDR 22,000 per box and an initial investment of IDR 412,740, the business reached a profit of IDR 845,102 in the first month, with a projected break-even point of approximately 9.1 months. The results suggest that savory bakpia with tuna and tempeh sambal matah has high potential as an innovative local food product and business startup, provided consistent marketing strategies and product development are maintained.